2015
DOI: 10.1123/jpah.2014-0251
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders, Physical Activity, and Sedentary Behavior Among U.S. Adults: National Health and Nutrition Examination Survey

Abstract: These results indicate that middle-aged adults who are less active may have increased likelihoods of SD. It is important for health care professionals to continue developing methods for increasing PA to decrease the risk of SD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…Other studies that indicate the need for bettering fitness to improve sleep quality include those of Farnsworth et al and McClain et al [43, 44]. The former team of investigators found that individuals with low levels of sedentary behavior, obesity, and physical activity were not significantly associated with developing a sleep disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that indicate the need for bettering fitness to improve sleep quality include those of Farnsworth et al and McClain et al [43, 44]. The former team of investigators found that individuals with low levels of sedentary behavior, obesity, and physical activity were not significantly associated with developing a sleep disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The former team of investigators found that individuals with low levels of sedentary behavior, obesity, and physical activity were not significantly associated with developing a sleep disorder. Meanwhile those with low levels of sedentary behavior and physical activity but high levels of obesity had an elevated risk of a sleep disorder [43]. The significance of this finding is that key measures of fitness and body composition may be associated with risk of sleep disorders and therefore poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of physical activity were observed in younger and middle-aged women who achieved at least 8 hours of sleep per day [18]. Low levels of physical activity have been associated with sleep disorders [19]. In terms of sleep chronotype, a small number of studies have shown later bedtime, waketime, and midpoint of sleep to be associated with lower levels of physical activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Identified risk factors for sleep problems include socio-demographics such as age 18,19 ; gender 18 ; race 20 ; marital status 21 ; education 22 ; and dependent family members. 23 Sleep problems have also been linked to lifestyle factors such as smoking 24 and physical activity 25 ; and health conditions such as obesity, 26 chronic diseases, 27 and musculoskeletal pain. 28 …”
Section: Introductionmentioning
confidence: 99%